2022
DOI: 10.1186/s13584-022-00526-9
|View full text |Cite
|
Sign up to set email alerts
|

Results of the national biomonitoring program show persistent iodine deficiency in Israel

Abstract: Background Adequate iodine intake is essential for human health, for normal thyroid function, and for attainment of full intellectual potential in children. In light of Israel's lack of a mandatory salt fortification policy, heavy reliance on desalination and low iodine intake from dairy products and seafood, there is concern in Israel that the population is iodine deficient. Indeed, the first Israeli National Iodine Survey in 2016 found a median urinary iodine concentration (UIC) of 83 µg/L am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…It may be desirable to develop a rapidly adaptable and regional electronic tool for detecting iodine intake in public. Unlike Israel, other developed countries have professional software that may assist RDs in calculating iodine intake, although they cannot modify nutrition, and highlighting nutritional errors [9][10][11][12]16,29]. Accurately evaluating annual chemical iodine intake is close to impossible.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It may be desirable to develop a rapidly adaptable and regional electronic tool for detecting iodine intake in public. Unlike Israel, other developed countries have professional software that may assist RDs in calculating iodine intake, although they cannot modify nutrition, and highlighting nutritional errors [9][10][11][12]16,29]. Accurately evaluating annual chemical iodine intake is close to impossible.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent national iodine survey, the iodine status among pregnant women residing in this sub-district was similar to that of the overall pregnant women population (64 µg/L vs. 61 µg/L, respectively), as assessed by median UIC [4]. Although WHO recommends USI as a method for achieving and maintaining adequate iodine intake in the public, Israel remains one of the last developed countries to have no policy mandating salt fortification [6,12]. It is remarkable that this policy gap exists even though iodine deficiencies (whether mild, moderate, or severe) affect populations at all levels of economic development [13].…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…According to the Israel Ministry of Health (2017), drinking water from different nondesalinated sources contains varying concentrations of iodine (2-150 µg I L -1 ), but these results do not reflect the real situation with the concentration of iodine in end-user taps [18]. Barnett-Izhaki et al (2022) have noted that non-desalinated water in Israel has relatively low iodine levels (4-20 µg I L -1 ) [19]. Ovadia et al (2013) showed possible iodine deficiency among 76% of the participants, examined in Ashkelon District in Israel.…”
Section: Introductionmentioning
confidence: 99%